CHANGES IN THE SPANISH FAMILY THROUGH THE SPANISH PRESS: THE EMERGENCE OF A NEW PATTERN OF PATERNITY AT THE END OF THE NINETEENTH CENTURY - Crespo Sánchez, Francisco Javier; Hernández Franco, Juan (Revista de Historia Social y de las Mentalidades, 2017)
This work wants to research how family changed  through the study of the model of paternity which  was settled from the late nineteenth to the early  twentieth centuries; so, the main objectives are  to understand how the father figure was set and  which factors were part of his idiosyncrasy.  With this aim, on one hand, it has analyzed their  realities within the family home, confirming its  role such as the authority of the house and his  work as an educator of their children; on the other  hand, this paper focuses on the experiences of  fatherhood away from home, investigating how  it was his duty to earn money and to support the  family and pointing out which dangers had the  father in the public sphere (alcohol, gambling and  prostitution). The source for this analysis was the  Spanish press of the period, analyzing its speeches  and the models of parenthood proposed. Finally,  with all this, it was proposed to understand if the  paradigm of fatherhood manifested new features  or if he kept building from traditional values and  practices.
Keywords: Family; Paternity; Home; Education; Press